2017
DOI: 10.1158/2326-6066.cir-16-0398
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD47 and Autophagy Elicited Enhanced Antitumor Effects in Non–Small Cell Lung Cancer

Abstract: CD47-specific antibodies and fusion proteins that block CD47-SIRPa signaling are employed as antitumor agents for several cancers. Here, we investigated the synergistic antitumor effect of simultaneously targeting CD47 and autophagy in nonsmall cell lung cancer (NSCLC). SIRPaD1-Fc, a novel CD47-targeting fusion protein, was generated and was found to increase the phagocytic and cytotoxic activities of macrophages against NSCLC cells. During this process, autophagy was markedly triggered, which was characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 51 publications
(57 reference statements)
2
58
0
Order By: Relevance
“…Depending on cell type and stimulus, autophagy could be a double-edged sword in cancer treatment—chemotherapeutics could either initiate cytoprotective autophagy or induce autophagic tumor cell death [ 21 , 26 , 28 , 29 , 41 , 42 , 43 ]. Most of the time, especially in amino acid deprivation therapy, autophagy could degrade superfluous or dysfunctional proteins and organelles to supply nutrients and materials for dying tumor cells, thus served as protective mechanism [ 21 , 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on cell type and stimulus, autophagy could be a double-edged sword in cancer treatment—chemotherapeutics could either initiate cytoprotective autophagy or induce autophagic tumor cell death [ 21 , 26 , 28 , 29 , 41 , 42 , 43 ]. Most of the time, especially in amino acid deprivation therapy, autophagy could degrade superfluous or dysfunctional proteins and organelles to supply nutrients and materials for dying tumor cells, thus served as protective mechanism [ 21 , 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that EB1089 induces a novel cytostatic form of autophagy suppressing NSCLC proliferation [ 166 ]. Additionally, Zhang et al have shown that simultaneous targeting of CD47 and autophagy in NSCLC xenograft models enhance antitumor activity through the activation of caspase-3, recruitment of macrophages, and overproduction of ROS [ 167 ].…”
Section: Autophagy and Cancermentioning
confidence: 99%
“…[ 77 ] A CD47-targeting fusion protein SIRPα-Fc was reported to activate macrophages in NSCLC xenograft mice, probably mediated by inactivation of mammalian target of rapamycin and reactive oxygen species, and was enhanced by simultaneously targeting autophagy. [ 78 ] Caspase-3/7 were poorly activated in NSCLC, [ 77 ] while caspase-3 was activated in CD47-targeting therapy, indicating an acceleration of apoptosis. [ 78 ] An anti-CD47 small interfering RNA (siRNA) was also shown to be effective in inhibiting tumor invasion and metastasis in NSCLC cell lines.…”
Section: Co-inhibitory Macrophage Checkpointsmentioning
confidence: 99%
“…[ 78 ] Caspase-3/7 were poorly activated in NSCLC, [ 77 ] while caspase-3 was activated in CD47-targeting therapy, indicating an acceleration of apoptosis. [ 78 ] An anti-CD47 small interfering RNA (siRNA) was also shown to be effective in inhibiting tumor invasion and metastasis in NSCLC cell lines. [ 75 ] In addition, Wu et al [ 79 ] explored a novel strategy to deliver anti-CD47 siRNA to kill lung cancer cells precisely without adverse effects on CD47-expressing platelets and red blood cells, exploiting the excessive glutamine demand of tumor cells.…”
Section: Co-inhibitory Macrophage Checkpointsmentioning
confidence: 99%